2022
DOI: 10.3390/catal12060630
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Kinetic Modeling of CO2-Based Fischer–Tropsch Synthesis

Abstract: The direct hydrogenation of CO2 to long-chain hydrocarbons, so called CO2-based Fischer–Tropsch synthesis (FTS), is a viable future production route for various hydrocarbons used in the chemical industry or fuel applications. The detailed modeling of the reactant consumption and product distribution is very important for further process improvements but has gained only limited attention so far. We adapted proven modeling approaches from the traditional FTS and developed a detailed kinetic model for the CO2-FTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Before discussing the experimental results, it must be emphasized that, in principal, it is impossible to differentiate between secondary reactions of recycled products and a shift in the primarily formed products based on the obtained product spectrum. In a previous study, we investigated the change in product composition under once-through conditions for greatly varying residence times . A slight change in the average chain length of the product could be observed for different residence times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before discussing the experimental results, it must be emphasized that, in principal, it is impossible to differentiate between secondary reactions of recycled products and a shift in the primarily formed products based on the obtained product spectrum. In a previous study, we investigated the change in product composition under once-through conditions for greatly varying residence times . A slight change in the average chain length of the product could be observed for different residence times.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we investigated the change in product composition under once-through conditions for greatly varying residence times. 27 A slight change in the average chain length of the product could be observed for different residence times. The composition within one carbon number, however, appeared to be relatively independent of the residence time.…”
Section: Product Distributionmentioning
confidence: 93%
See 1 more Smart Citation
“…In power-to-liquid processes and in biomass-to-liquid approaches, relevant amounts of CO 2 in the FT feed gas typically make a reverse WGS reaction step before the FT reactor mandatory. However, direct CO 2 hydrogenation would eliminate the need for this additional level of complexity (Brübach et al, 2022).…”
Section: Co 2 Hydrogenationmentioning
confidence: 99%
“…Recently, a microkinetic approach was applied that allowed obtaining the models successfully describing reagent consumption and products formation as well as hydrocarbon distribution of CO2 hydrogenation that were demonstrated in works. [57,58] From the presented works one can see the complexity of kinetic modeling of CO2 hydrogenation to hydrocarbons. In our work we demonstrated that neural KCNODE could be successfully applied for describing the kinetics of this complicated reaction.…”
Section: Modelling Of Co 2 Hydrogenation To Hydrocarbonsmentioning
confidence: 99%